Characterization of Eimeria tenella sporozoite antigen by sodium dodecyl sulphate-polyacrylamide gel electrophoresis - Garg, Rajat; Banerjee, D P; Kumar, Sanjay (The Indian Journal of Animal Sciences, 2012)
Purified sporozoites of Eimeria tenella were disrupted by sonication on ice and then centrifuged at 10 000 g for 1 hr at 4Â°C. The supernatant thus obtained was used as 11 soluble sporozoite antigen. Protein profile of this antigen was determined by SDS-PAGE which revealed 16 discrete polypeptide bands ranging from 30 to 220 kD molecular weight. Out of these, 6 bands seemed to be the major ones on the basis of their appearance.